2017
DOI: 10.1167/iovs.17-22399
|View full text |Cite|
|
Sign up to set email alerts
|

Optic Nerve Hypoplasia Is a Pervasive Subcortical Pathology of Visual System in Neonates

Abstract: PurposeOptic nerve hypoplasia (ONH) is the most common cause of childhood congenital blindness in developed nations, yet the fundamental pathobiology of ONH remains unknown. The objective of this study was to employ a ‘face validated' murine model to determine the timing of onset and the pathologic characteristics of ONH.MethodsBased on the robust linkage between X-linked CASK haploinsufficiency and clinically diagnosed ONH, we hypothesized that heterozygous deletion of CASK (CASK(+/−)) in rodents will produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…Relatively preserved function produces microcephaly without any retinal or optic nerve defect, complete loss of function produces ONH, and mutations with functional loss in between the two produces a retinal defect with a delayed onset and thus appears as degenerative changes in childhood. We have shown that CASK haploinsufficiency in mice produces ONH with a reduction in the number of retinal ganglion cells but no change in retinal lamination nor a reduction in the thickness of the photoreceptor cell layer (Liang et al, 2017). Does CASK play a developmental role in the retina outside of the retinal ganglion cells?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively preserved function produces microcephaly without any retinal or optic nerve defect, complete loss of function produces ONH, and mutations with functional loss in between the two produces a retinal defect with a delayed onset and thus appears as degenerative changes in childhood. We have shown that CASK haploinsufficiency in mice produces ONH with a reduction in the number of retinal ganglion cells but no change in retinal lamination nor a reduction in the thickness of the photoreceptor cell layer (Liang et al, 2017). Does CASK play a developmental role in the retina outside of the retinal ganglion cells?…”
Section: Discussionmentioning
confidence: 99%
“…Girls with heterozygous LOF mutations typically exhibit postnatal microcephaly, severe global developmental delays, ponto-cerebellar hypoplasia, motor incoordination, hypotonia, seizures and ophthalmological phenotypes like optic nerve atrophy (ONA) and optic nerve hypoplasia (ONH) (Burglen et al, 2012; Moog et al, 2011). The brain phenotypes seen in humans can be faithfully replicated in female mice by deleting a single allele of the CASK gene, indicating that CASK has a highly conserved role in mammals (Liang et al, 2017; Srivastava et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on our results, we hypothesized that LRRTM1-neurexin interactions are critical for the formation of complex RG synapses. Although the necessity of neurexins in retinogeniculate connectivity has yet to be thoroughly examined, the loss of CASK, a MAGUK protein necessary for trafficking neurexins to the presynaptic membrane, leads to abnormal retinogeniculate connectivity and optic nerve hypoplasia ( LaConte et al, 2016 ; Srivastava et al, 2016 ; Moog et al, 2011 ; Liang et al, 2017 ).…”
Section: Disscussionmentioning
confidence: 99%
“…Therefore, based on our results, we hypothesized that LRRTM1-neurexin interactions are critical for the formation of complex RG synapses. Although the necessity of neurexins in retinogeniculate connectivity has yet to be thoroughly examined, the loss of CASK, a MAGUK protein necessary for trafficking neurexins to the presynaptic membrane, leads to abnormal retinogeniculate connectivity and optic nerve hypoplasia (LaConte et al, 2016, Moog et al, 2011, Liang et al, 2017.…”
Section: Lrrtm1 As a Target-derived Synaptic Organizer In Visual Thalmentioning
confidence: 99%